Dynamic capabilities as applied to sustainable organizing theory: Cases from agri-social enterprises - Bolinao, James Marius (Animo Repository, 2022)
Purpose – Dynamic capabilities, a conventional organization theory, are viewed as a viable response to such turbulent environments. With agri-social enterprises constantly being pressured to adapt, this study explored their dynamic capabilities and their synergies with Newtonian and quantum views in sustainable organizing theory. Design/methodology/approach – The authors designed a research framework connecting dynamic capabilities with sustainable organizing theory. The framework was tested through a qualitative, multiple case study method featuring three agri-social enterprises. Findings – After a cross-case analysis of all three cases, findings show that a firm’s sensing, learning, integrating, and coordinating capabilities are related to sustainable organizing theory. Dynamic capabilities, therefore, can be applied to identify Newtonian and quantum organizations. Research limitations/implications – The study was limited to cases from agri-social enterprises. In the future, researchers may expand the scope to include social enterprises in different industries. Practical and social implications – Analyzing dynamic capabilities in light of quantum views is relevant for policymakers, managers, and researchers as they navigate in turbulent environments. Originality/Value – This pioneering study explored and integrated mainstream management theory with new, emerging ideologies in sustainable organizing theory. Dynamic capabilities, therefore, are seen in a different light; a theory beyond competitive advantage.